2020
DOI: 10.1101/2020.03.19.998658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human prostate cancer bone metastases have an actionable immunosuppressive microenvironment

Abstract: Cancer-related mortality due to solid tumor malignancies is overwhelmingly due to the development and progression of metastases. In advanced prostate cancer, metastases most often involve the bone 1 and generally represent incurable disease. It remains unclear what aspects of the bone marrow microenvironment make it hospitable to metastatic dissemination. Similarly, the impact of the metastatic tumor on hematopoiesis and the marrow immune response is poorly understood. Here we take advantage of rare spinal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Much of our knowledge derives from microarray analysis on laser capture microdissected tumor and stromal areas [164,165] and xenograft models [44], which allow distinction of the stroma, provided by the host organism, from the human tumor cells. Nevertheless, the recent development of techniques such as next generation sequencing and single cell-analysis is changing our understanding of the landscape of PCa reactive stroma in bone metastasis, as well as in primary PCa, in terms of the multi-omic molecular profiling and elucidation of cellular processes occurring in distinct stromal cell populations [58,60,166].…”
Section: Role Of Cafs In Pca Bone Metastasismentioning
confidence: 99%
“…Much of our knowledge derives from microarray analysis on laser capture microdissected tumor and stromal areas [164,165] and xenograft models [44], which allow distinction of the stroma, provided by the host organism, from the human tumor cells. Nevertheless, the recent development of techniques such as next generation sequencing and single cell-analysis is changing our understanding of the landscape of PCa reactive stroma in bone metastasis, as well as in primary PCa, in terms of the multi-omic molecular profiling and elucidation of cellular processes occurring in distinct stromal cell populations [58,60,166].…”
Section: Role Of Cafs In Pca Bone Metastasismentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] for statistical analysis. To incorporate the unique effect of each donor on which multiple measurements were taken, we applied Linear Mixed Models (LMM) with random effect using the 'lme' function of 'nlme' package (16)(17)(18). The significance level was set to 1% (α=0.01).…”
Section: Competing Interest Declarationmentioning
confidence: 99%
“…S7A,B). As changes in proportion of one subtype could potentially skew the representation of other subtypes, we applied Compositional Data Analysis ( 18 ) techniques to calculate robust estimates of compositional changes (see Methods). This analysis confirmed that schizophrenia was linked to a general increase in most subtypes of L2_3_CUX2 and L4_5_FEZF2 families of principal neurons, and a decrease in several interneuron subtypes, most notable for SST_CALB1 (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Our analysis has so far primarily focused on infiltrating T cells, but the immune microenvironment clearly contains other elements, especially in advanced disease. Single-cell RNA sequencing of advanced PCa bone metastases has revealed depletion of B cells and an increase in M2-polarized tumor-associated macrophages (47). This is associated with increased exhaustion and decreased cytotoxicity programs in cytotoxic T lymphocytes in a CCR6-CCL20-dependent manner.…”
Section: Discussionmentioning
confidence: 99%